Pineapple Lectin AcmJRL Binds SARS‐CoV‐2 Spike Protein in a Carbohydrate‐Dependent Fashion. (23rd December 2022) - Meiers, Joscha; Dastbaz, Jan; Adam, Sebastian; Rasheed, Sari; Kirsch, Susanne H.; Meiser, Peter; Gross, Peter; Müller, Rolf; Titz, Alexander
Abstract: The highly glycosylated spike protein of SARS‐CoV‐2 is essential for infection and constitutes a prime target for antiviral agents and vaccines. The pineapple‐derived jacalin‐related lectin AcmJRL is present in the medication bromelain in significant quantities and has previously been described to bind mannosides. Here, we performed a large ligand screening of AcmJRL by glycan array analysis, quantified the interaction with carbohydrates and validated high‐mannose glycans as preferred ligands. Because the SARS‐CoV‐2 spike protein was previously reported to carry a high proportion of high‐mannose N ‐glycans, we tested the binding of AcmJRL to the recombinantly produced extraviral domain of spike protein. We could demonstrate that AcmJRL binds the spike protein with a low‐micromolar K D in a carbohydrate‐dependent fashion. Abstract : It's down to the carbohydrate : Pineapple lectin AcmJRL was characterised by two distinct glycan arrays, and a competitive binding assay was established. Further, it was shown that AcmJRL binds SARS‐CoV‐2 S‐protein in a carbohydrate dependent‐fashion.